2021
DOI: 10.14740/jocmr4543
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obesity and Cancer Mortality: An Internal Medicine Outpatient Clinic Perspective

Abstract: Background: Obesity is one of the leading preventable causes of cancer that has a causal relationship with cancers of esophagus, breast and colon. Paradoxically, there are studies demonstrating that obesity is associated with improved survival in cancer patients. The aim of our study was to investigate the association of obesity and cancer mortality in adult patients.Methods: Retrospective medical record review of 784 adult patients was performed who had a diagnosis of cancer and who were seen in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…It is worth noting, however, that some studies observed that HbA1c was positively associated with cancer mortality. 45,46 Many guidelines have started to recommend non-fasting lipids (total, HDL & LDL cholesterol as well as triglyceride) as the standard for cardiovascular risk assessment. 47,48 The current study suggests that non-fasting glucose (PPG4-7.9h) may be used for cancer mortality risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that some studies observed that HbA1c was positively associated with cancer mortality. 45,46 Many guidelines have started to recommend non-fasting lipids (total, HDL & LDL cholesterol as well as triglyceride) as the standard for cardiovascular risk assessment. 47,48 The current study suggests that non-fasting glucose (PPG4-7.9h) may be used for cancer mortality risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have evaluated the association between Hba1c levels and the mortality of multiple cancers [ 20 , 32 , 33 , 34 ]. A previous study with 2,686 participants without a history of diabetes and a mean duration of follow-up of 7.54 ± 2.1 years failed to show any significant increase in cancer mortality in the HbA1c < 6.5% group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rising HbA1c and increasing age were associated with increased cancer mortality (28). We now have moderate-certainty evidence that periodontal treatment using subgingival instrumentation significantly improves glycemic control in people with both periodontitis and DM compared to no treatment or usual care (29). The study findings support the Mediterranean dietary model as a suitable model for T2DM and the concept that the beneficial health effects of the Mediterranean diet lie primarily in the synergy among various nutrients and foods rather than on any individual component (30).…”
Section: Discussionmentioning
confidence: 99%